RUUÂ KESETARAANÂ DANÂ KEADILANÂ GENDER: PembahasanÂ dariÂ PerspektifÂ TeologiÂ adâ€DinÂ Alâ€QayyimÂ dalamÂ Alâ€Qurâ€™an - Ilyas, Hamim (Sunan Kalijaga State Islamic University & The Asia Foundation, 2012)
This article discusses of KKG in theological perspective al-din al-Qayyim in alQuran. In this case, this perspective is something new developed. The old conception that developed in the community is always viewed from the perspective of law or jurisprudence. Theological concept that carried the authors in this case done in depth through the verses found in the Qur'an in the context of al-din al-Qayyim. Jurisprudence approach commonly used for this are not able to address the true essence of the problem. Such an approach makes fiqh not able to uncover the goals and ideals of the Qur'an in realizing real goodness in all areas of life, including the nine areas set out in the Bill. Through theological approach al-din al-Qayyim can manifest a new enlightenment.